The Influence of Health Education Using Video Media on Knowledge of Anemia Prevention in Adolescent Girls - Maesaroh, Siti; Sukini, Tuti; Chunaeni, Siti (Midwifery and Nursing Research, 2024)
Background : Anemia in adolescent girls (rheumatism) will have an impact on health. The government's efforts to prevent and control anemia in adolescents include a program that provides iron tablets to adolescents every year. Providing information or knowledge can be done through health education. Several educational media developments with advanced technology have been carried out, such as through an audiovisual (video) approach. Not only does it have an attractive appearance, animated videos make the information provided last longer in the memory and make respondents satisfied/happy. The effectiveness of a video can also be seen from the length of time the information can remain in a person's memory. The aim of this research is to determine the effect of video media on knowledge of anemia prevention in adolescent girls.Methods : This type of research uses a quasi-experimental pretest-posttest group design. The population in the study was 58 respondents using a total sampling technique, with data analysis using the Mann Whitney test..Result : The results of the study showed that the knowledge of young women before providing health education using video media obtained results with a median of 21.97 with the lowest value being 12 and the highest value being 29. The knowledge of young women after providing health education using video media obtained results with a median of 26.62 with the lowest value being 21. and the highest score is 30. There is an influence of video media on knowledge of anemia prevention in young women (P value 0.000).Conclusions : Health workers, especially midwives, in providing health services can provide information to the public, especially young women, especially about anemia by encouraging a program to take Fe tablets correctly and appropriately.